The Development and Implementation of Artificial Intelligence Technology in a Manufacturing Company in the Banten Province - Arta Rusidarma Putra; Irma Nurmala Dewi (Universitas Veteran Bangun Nusantara Sukoharjo, 2025)
The heterogeneous backgrounds of employees within manufacturing firms contribute to disparities in their preparedness to embrace artificial intelligence. A prominent concern that engenders scepticism among prospective AI users is data security. The focus of the study is the use of AI technology in the context of companies engaged in the manufacturing industry in Banten Province, with the aim of understanding the views of potential AI users and the factors that influence their willingness to utilize this technology. This study aims to investigate the integration of AI technology in everyday tasks from the viewpoint of prospective AI users. The research sample comprised 100 respondents, potential AI users, who were employees at various levels within multiple manufacturing industries in Banten. The data analysis method used a mixed method with analysis techniques using regression tests and quantitative data with thematic analysis for qualitative data. The regression test results revealed that attitudes significantly impacted the intention to use artificial intelligence. Individual attitudes toward artificial intelligence (AI) can influence the desire to use it. Certain users are prepared to utilize AI, while others remain apprehensive due to concerns regarding adverse effects, including data security and privacy risks. Some users are also anxious that AI will replace their jobs. This variation is affected by multiple factors, including the profession, the hierarchical level, and the tasks' intricacy.